Correlation of non-auditory comorbidities and hearing loss in chronic subjective tinnitus patients: a retrospective database study - Konstantin Tziridis; Benjamin Neubert; Anna Seehaus; Patrick Krauss; Patrick Krauss; Achim Schilling; Achim Schilling; Petra Brüggemann; Birgit Mazurek; Holger Schulze (Frontiers in Neurology)
BackgroundTinnitus is a symptom often associated with hearing loss (HL). Its development and progression are still not completely clear, as the heterogeneity of tinnitus-related HL data is high. Here, we attempt to investigate whether a part of this variance can be correlated with single or combinations of non-auditory comorbidities using pure-tone audiometric data in a collective of chronic subjective tinnitus patients.MethodsThe information of 136 tinnitus patient files was extracted retrospectively. The patients did not suffer from any auditory impairment except a possible HL and tinnitus; non-auditory comorbidities were identified from the files and categorized by their ICD-10 category. Comorbidity classes were endocrine/metabolic diseases, psychiatric/behavioral disorders, diseases of the central nervous system, diseases of the circulatory system, diseases of the respiratory system, diseases of the digestive system, and muscle-skeletal diseases. The pure-tone audiometry data, as well as tinnitus pitch and loudness, were correlated with their non-auditory comorbidity classes and patients’ age group using non-parametric and parametric analyses, where appropriate.ResultsDepending on the age group, the number of comorbidities could lead to a significant increase or decrease in HL. Only in older patients, a linear correlation between the number of non-auditory comorbidities and an increase in HL could be found. Moreover, the correlation between maximal HL frequency and tinnitus frequency can only be seen in specific age and comorbidity-number groups. Only some specific non-auditory comorbidity classes showed significant effects (decrease or increase) on HL in specific age groups.ConclusionTaken together, we argue that in future tinnitus patient studies, non-auditory comorbidities should be taken into account as possible covariables that might explain the variance found in the auditory threshold development of these patients.